001. EGFR mutations in Greek patients with lung adenocarcinoma: a multi-center study (preliminary results) - Zarogoulidis, Pavlos (J Thorac Dis, 2015)
BACKGROUND: Integration of mutational epidermal growth factor receptor (EGFR) profiling to identify driver alterations in a clinical setting, is necessary to facilitate personalized lung cancer medicine. A tumor genotyping EGFR panel was developed and the Greek Mutation Study was initiated as a prospective tumor genotyping study. This study reports the frequency of driver genetic alterations in Greek lung adenocarcinoma patients, and epidemiology correlations with EGFR genotype. METHODS: Between November 2012 and June 2014, 211 lung adenocarcinoma patients were included in this study. EGFR mutations were tested in lung cancer tissues and histologic specimen. All patients completed informed consent. The method was high resolution melting analysis (HRMA) about mutations 18-21 and further analysis with method sequencing-ABI prism 3130 sequencer (DNA). Eighteen Surgically resected tissues (8.5%), 174 tumor biopsies (82%) and 19 (9%) body cavity fluids were collected and tested for EGFR mutations. We describe clinical and epidemiological profile of EGFR positive adenocarcinoma patients. RESULTS: Genetic EGFR positive mutations were detected in 10.8% (24 of 221) of all patients, fifteen women and nine men. All women were nonsmokers (100%) and seven of nine (78%) men were smokers. Mean age of this group was 64.3 years old. Eighteen patients were with stage IV and rest of them IIIa. None of them was operable. CONCLUSIONS: This is one report of tumor EGFR positive Greek patients with adenocarcinoma. These data suggest that patients profiling data using a mutational testing platform would be valuable for observation for each group of patients helping clinical doctor for further molecular-targeted therapeutics in lung cancer.